Effectiveness of Manual and Electrical Acupuncture for Chronic Non-speciﬁc Low Back Pain: A Randomized Controlled Trial - Josielli Comachio; Carla C. Oliveira; Ilton F.R. Silva; Mauricio O. Magalhães; Amélia P. Marques (Medical Association of Pharmacopuncture Institute, 2020)
Background: Low back pain is a common condition that can be effectively treated by acupuncture. However, several treatment point prescriptions and further electrical needle stimulation (i.e., local acupoints, distal acupoints, and sensitized acupoints) may be used. There is an implicit yet unexplored assumption about the evidence on manual and electrical stimulation techniques. Objective: The present study aims to identify effectiveness of electroacupuncture (EA) and manual acupuncture (MA) on pain and disability in patients with chronic nonspecific low back. Methods: This study is a randomized controlled clinical trial. Sixty-six patients between 20 and 60 years of age with non-specific chronic low back pain experiencing low back pain lasting for at least the previous three months and ≥3 points on a 10 numerical analogic scale. Patients diagnosed with chronic LBP were assigned to receive either 12 sessions of MA or EA. The primary outcomes measurements were pain intensity on Numeric Rating Scale and disability by Roland Morris Disability Questionnaire. Results: The participants reported improvements post-treatment to pain intensity and disability respectively; however, no differences between groups were observed. Regarding the secondary outcomes, we observed a between-group difference only for kinesiophobia in favor of the manual acupuncture group (difference = −4.1 points, 95% CI = −7.0 to −1.1). The results were maintained after 3 months of follow-up. Conclusion: The study provides evidence that EA is not superior to MA treatment. Both therapies had similar efficacy in reducing pain and disability for chronic nonspecific low back pain.